(untitled) (Revista Ciencia Agraria, 2023)
Micro, Small and Medium Enterprises (MSMEs) represent a large part of the economic power of various countries. In the specific case of Mexico, 99% of the companies are in this classification, which is why this essay seeks to reach people interested in starting a business, in order to show what are the characteristics of entrepreneurs, what they will require, as well as an introduction to the administrative process, which will become a cycle throughout the operation of the business. It is evident that the main characteristics of the entrepreneur considered by the literature consider people to be innovative, creative, organized, structured and with a large social component. It is of the utmost importance that society supports entrepreneurs so that they can develop their entrepreneurial skills and abilities, as well as generating public policies and the creation of favorable environments for entrepreneurship can help reduce barriers to entry and improve conditions for entrepreneurship, business creation and growth.